Rationing Rotational Magnet Cochlear Implant Technology in a Single Payer Healthcare System. (August 2021) - Pisa, Justyn; Andrews, Colin; Hochman, Jordan B.
Introduction: In a publicly funded health care system, fiscally responsible management of any program is required. This is especially pertinent as evolving technology and associated incremental costs, places pressure on device availability within a fixed funding envelope. The application of rotational magnet technology and associated escalating surgical wait times must be justified to patients and the single-payer system. We present a single cochlear implant center's attempt at a rationing schema for magnetic resonance compatible cochlear implantation. Contrasting approaches to rationing care are evaluated and deliberated. Methods: Based on a comparison of magnetic resonance imaging (MRI) rates within the general population to our cochlear implant (CI) cohort, we attempt the development of a decision-making schema that maximizes the number of patients to receive a CI while rationing the distribution of a rotational magnet technology to similarly situated individuals most likely to benefit. Results: We elect to provide rotational magnet technology to select patient cohorts. This is based on the dominant imaging needs of these populations and the probability of requiring recurrent imaging studies. We consider this an ethical approach grounded in the egalitarian principle of equality of opportunity within cohorts of patients. Conclusion: Given finite resources, increasing per unit cost will unavoidably extend wait times for adult patients. Our approach does not afford similar implant devices for all patients, but rather all similarly situated individuals. Therefore, access to a scare medical resource requires program rigor and a formalized policy around candidacy for emergent technology.